2019
DOI: 10.1038/s41598-019-55840-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of new microalgae-based sourdough “crostini”: functional effects of Arthrospira platensis (spirulina) addition

Abstract: The aim of this work was to evaluate the influence of Arthrospira platensis F&M-C256 (spirulina) incorporation on the nutritional and functional properties of “crostini”, a leavened bakery product largely consumed in Italy and Europe. Sourdough was used as leavening and fermentation agent and three concentrations of A. platensis F&M-C256 were tested: 2%, 6% and 10% (w/w). Despite a lower volume increase compared to the control, the A. platensis F&M-C256 “crostini” doughs reached a technological appropriate vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 64 publications
1
41
1
5
Order By: Relevance
“…In the pasta, the L* value reduced from 62.83 to 30.72, while a* and b* values ranged from 1.14-16.40 to −8.55-6.00, respectively [80]. Similar findings for crostini are reported, L* (69 to 26) a* (0.7-0.3), b* (16-1.2), and chroma (16-1.2) values decreased, and the hue ( • ) values were found in a range of 77-87 [69]. The hue angle for control and AWP were lower than 100 • (79-85) compared to all SPP enriched pasta (≥100), indicating red-yellow color and higher saturation (chroma value).…”
Section: Fettuccine Pastasupporting
confidence: 85%
See 1 more Smart Citation
“…In the pasta, the L* value reduced from 62.83 to 30.72, while a* and b* values ranged from 1.14-16.40 to −8.55-6.00, respectively [80]. Similar findings for crostini are reported, L* (69 to 26) a* (0.7-0.3), b* (16-1.2), and chroma (16-1.2) values decreased, and the hue ( • ) values were found in a range of 77-87 [69]. The hue angle for control and AWP were lower than 100 • (79-85) compared to all SPP enriched pasta (≥100), indicating red-yellow color and higher saturation (chroma value).…”
Section: Fettuccine Pastasupporting
confidence: 85%
“…Even though there are no studies of pasta enriched with protein isolated from spirulina, pasta elaborated using spirulina biomass (10%) has shown lower protein values, fiber, and carbohydrates (14, 7.8, and 56%, respectively) and a higher content of fat (17%) than AWP-SPP (10%) [68]. Protein content reported for crostini bread prepared with 10% of spirulina was 16.7%, lower than the presented values in this study [69]. In addition to the protein compounds, one of the principal nutritional contributions of both amaranth flour and SPP in pasta was the mineral content denoted by the ash component (Table 6).…”
Section: Fettuccine Pastacontrasting
confidence: 79%
“…A. platensis is considered safe in many countries (e.g., in EU, Australia, United States) and widely commercialized as dietary supplement (powder, capsules, or tablets) (Borowitzka, 2013). A. platensis biomass is also increasingly used as food ingredient, incorporated into gluten-free pasta (Fradinho et al, 2020), bakery products (Batista et al, 2017(Batista et al, , 2019Niccolai et al, 2019b), candies, yogurt, and soft drinks (Christaki et al, 2011;Niccolai et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…While, Siva Kiran et al [84] reported that the protein content in Spirulina is higher compared to other foods such as milk, chicken, beef, and some plants. In food application, Spirulina and Chlorella or its protein were incorporated in various types of food, such as milk-based products, bread, biscuits, instant noodles and pasta to produce protein-enriched functional food [85][86][87][88].…”
Section: Algal Proteinmentioning
confidence: 99%